Standard: Human gastric cancer organoids - Ronghui Tan; Fan Hong; Ting Wang; Nanshan Zhong; Hongling Zhao; Rui-hua Xu; Lin Shen; Yingbin Liu; Xuebiao Yao; Dongxi Xiang; Dong Gao; Jianping Xiong; et al. (Cell Regeneration)
Abstract Gastric cancer is one of the most common malignancies with poor prognosis. The use of organoids to simulate gastric cancer has rapidly developed over the past several years. Patient-derived gastric cancer organoids serve as in vitro models that closely mimics donor characteristics, offering new opportunities for both basic and applied research. The “Human Gastric Cancer Organoid” is part of a series of guidelines for human gastric cancer organoids in China, jointly drafted by experts from the Chinese Society for Cell Biology and its branches, and initially released on October 29, 2024. This standard outlines terminology, technical requirements, assessment protocols, and applies to production, evaluation procedures, and quality control for human gastric cancer organoids. The publication of this guideline aims to assist institutions in endorsing, establishing, and applying best practices, advancing the international standardization of human gastric cancer organoids for clinical development and therapeutic application.